2005
DOI: 10.1161/01.atv.0000149141.81230.c6
|View full text |Cite|
|
Sign up to set email alerts
|

Vascular Injury Induces Expression of Periostin

Abstract: T issue remodeling after injury involves the coordinate regulation of numerous genes, including those involved with extracellular matrix (ECM) synthesis and turnover, cell adhesion, and cell migration. Major components of the ECM include structural proteins and a number of soluble ECMassociated proteins. The soluble ECM-associated proteins include SPARC, lumican, and the fasciclin domain-containing proteins ig-H3 and periostin. Periostin, originally named osteoblast-specific factor-2 (Genbank D13664) was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(87 citation statements)
references
References 43 publications
7
79
1
Order By: Relevance
“…This hypothesis is consistent with the cells of the tooth mesenchyme that also highly express periostin and undergo an EMT (Kruzynska-Frejtag et al, 2004). During cardiovascular development initially, periostin is expressed in response to signaling from the BMP and TGF-␤ family of growth factors (Horiuchi et al, 1999;Ji et al, 2000;Hall et al, 2001;Kruzynska-Frejtag et al, 2001Lindner et al, 2004). However, as development progresses, the heart must withstand the increasing influence of hemodynamic sheer stress (Stekelenburg et al, 2004).…”
Section: Resultssupporting
confidence: 64%
“…This hypothesis is consistent with the cells of the tooth mesenchyme that also highly express periostin and undergo an EMT (Kruzynska-Frejtag et al, 2004). During cardiovascular development initially, periostin is expressed in response to signaling from the BMP and TGF-␤ family of growth factors (Horiuchi et al, 1999;Ji et al, 2000;Hall et al, 2001;Kruzynska-Frejtag et al, 2001Lindner et al, 2004). However, as development progresses, the heart must withstand the increasing influence of hemodynamic sheer stress (Stekelenburg et al, 2004).…”
Section: Resultssupporting
confidence: 64%
“…It is now generally accepted that tumour cells modify the composition of the adjacent stroma by secreting their own extracellular matrix proteins to create a permissive and supportive environment for their growth (Bissell and Radisky, 2001;Koninger et al, 2004). This hypothesis is supported by the observation that periostin transcription is upregulated in pulmonary smooth muscle cells exposed to hypoxic conditions (Li et al, 2004), in damaged myocardial tissues where migration and resistance of cells to apoptosis is essential (Lindner et al, 2005;Litvin et al, 2005) and in the area around developing teeth where intense cell traction and cell stress occur (Rios et al, 2005). Altogether, these data demonstrate that gain of adhesive interaction induced by overexpression of periostin through the desmoplastic stroma should confer to the cancer cells a selective advantage during the metastatic process and suggest that periostin could be considered as a new member of the matricellular family.…”
Section: Discussionmentioning
confidence: 95%
“…In the same context, we recently found that the expression of βig-h3 in cultured human monocyte-derived macrophages can be induced by tumor necrosis factor-α or IL-1β, inflammatory cytokines frequently increased in atherosclerotic microenvironment (data not published). Periostin, a matrix protein that is highly homologous to βig-h3, is also elevated in rat arteries after vascular injury and localized to smooth muscle cells of the neointima and adventitia and promotes migration of VSMCs (Lindner et al, 2005). Fas-1 domains of βig-h3 and related proteins such as periostin, stabilin-1, and stabilin-2 have been shown to interact with integrins and modulate cell adhesion and migration (Gillan et al, 2002;Kim et al, 2002;Politz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%